The effect of traditional congklak game-based learning on the numeracy achievement of second-grade elementary students - Beti Istanti Suwandayani; Lala Jelita Ananda; Rivatul Ridho Elvierayani; Erna Yayuk; Dyah Worowirastri Ekowati; Trisniawati; Zulkifley Bin Mohamed (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study examines the effect of traditional game-based learning with Congklak on numeracy achievement among second-grade elementary students. The study addresses the limited availability of experimental evidence on culturally grounded, non-digital games for early numeracy instruction. A pre-test–post-test control-group design was employed with 60 students (aged 7–8 years) from a public elementary school in Indonesia. Participants were assigned to either an experimental group receiving Congklak-based numeracy instruction or a control group receiving conventional textbook-based instruction for four weeks. Numeracy achievement was measured using the Numeracy Achievement Test (NAT), consisting of 30 dichotomously scored items covering number recognition, counting skills, and logical reasoning (score range 0–100; reliability coefficient α = 0.82). Data were analyzed using paired-samples and independent-samples t-tests. Results indicated significant pre-test–post-test improvement in both groups (p < .001). However, the experimental group achieved higher post-test scores (M = 78.47, SD = 6.92) than the control group (M = 66.13, SD = 7.25), with a statistically significant between-group difference, t (58) = 4.96, p < .001, d = 1.27. These findings suggest that integrating traditional Congklak-based activities into mathematics instruction can support early numeracy development through culturally responsive and play-based learning experiences.